2017
DOI: 10.1093/humrep/dex291
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis fertility index predicts live births following surgical resection of moderate and severe endometriosis

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
2
29
1
1
Order By: Relevance
“…To our knowledge, this is the first report validating EFI for the prediction of natural conception after surgery in Korean women with endometriosis. The EFI in this study showed a statistically significant correlation with natural pregnancy, similar to that of previous reports [12,14]. Even though our study population was small, only one woman with an EFI value < 4 was able to naturally conceive.…”
Section: Discussion/conclusionsupporting
confidence: 91%
See 2 more Smart Citations
“…To our knowledge, this is the first report validating EFI for the prediction of natural conception after surgery in Korean women with endometriosis. The EFI in this study showed a statistically significant correlation with natural pregnancy, similar to that of previous reports [12,14]. Even though our study population was small, only one woman with an EFI value < 4 was able to naturally conceive.…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…However, because EFI was assessed and recorded at the end of surgery in 61 of 68 patients, the effect of retrospective calculation on our results is likely to be minimal. It has also been suggested that EFI scoring has clinically meaningful results and additional potential use in retrospective settings [14,23]. In sensitivity analysis, such variation was marginally affected by the total EFI score [12], but the LF score still has several critical issues, such as intra/inter-observer variation.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median time to pregnancy was 12 months (95% CI 7–17 months), with 63% achieved by expectant management post‐operatively and 37% with assistance. In the most recent paper from our unit, we examined the use of the Endometriosis Fertility Index (EFI) only in stages III–IV disease, where there was a 63% live birth rate in an infertile population having surgery for endometriosis and 64% of these women spontaneously conceived. Perhaps the most important aspect of this study was that it tracked pregnancy to five years and showed that for women with an EFI score 9–10 that at one year, expectant management led to a live birth in 46% of women, 58% at two years and 91% at five years, with IVF only increasing this to 95% at five years.…”
Section: Surgery Endometriosis and Infertilitymentioning
confidence: 99%
“…Live births can accurately be predicted with the endometriosis fertility index (EFI), with adnexal function being the most important factor to predict non-assisted reproductive technology (non-ART) fertility or the requirement for ART. A total of 147 women (63%) had a live birth following surgery, 94 of them (64%) without ART [1]. Women with a high EFI score have excellent fertility prognosis and may be advised to try to become pregnant with timed intercourse compared to women with a low score, for which prompt referral to ART seems more reasonable [1].…”
Section: Introductionmentioning
confidence: 99%